Improving Tax Compliance Through E-Filing as a Moderating Variable - R.A. Widyanti Diah Lestari; Beni Hartono (Jurnal Akuntansi, 2025)
The research was conducted to examine how tariffs, sanctions, and awareness affect compliance and e-filing as a moderator. This study is included in the quantitative model. The population includes educators at a foundation engaged in education in Batam City. Purposive sampling based on specific criteria was used, resulting in 171 respondents. Data analysis used SmartPLS version 4.0.9 for the measurement model, structural model, and model goodness. The study shows that tariffs, sanctions, and awareness positively and significantly affect tax compliance. However, e-filing does not strengthen the effect of tariffs on compliance. In addition, the results show that e-filing has the ability to increase the effect of awareness and sanctions on compliance.